Comparison of the guidelines for colorectal cancer in Japan, the USA and Europe. Issue 1 (19th December 2017) - Shinagawa, Takahide; Tanaka, Toshiaki; Nozawa, Hiroaki; Emoto, Shigenobu; Murono, Koji; Kaneko, Manabu; Sasaki, Kazuhito; Otani, Kensuke; Nishikawa, Takeshi; Hata, Keisuke; Kawai, Kazushige; Watanabe, Toshiaki
Abstract: Colorectal cancer (CRC) is one of the most common cancers globally as well as in Japan and has shown a pattern of increasing incidence and mortality rates. Therefore, guidelines for CRC are considered to be crucial for establishing standard medical treatment not only in Japan but also around the world. In this article, we explain the features of the representative guidelines in Japan (Japanese Society for Cancer of the Colon and Rectum [JSCCR]), the USA (National Comprehensive Cancer Network [NCCN]) and Europe (European Society for Medical Oncology [ESMO]) and review the differences among these guidelines for CRC. We focus, in particular, on the descriptions of local treatments, including endoscopic treatment for CRC and transanal excision for lower rectal cancer; surgical treatments with lymph node dissection, including management of lower rectal cancer with lateral lymph node metastasis and laparoscopic surgery; and chemotherapy. Although the guidelines share basic principles, some details are different. Consulting the guidelines of various regions from around the world may aid in more precise and effective examination of the details and backgrounds of our own native guidelines.